EVALUATION OF THE SUCCESSFUL IMPLEMENTATION OF GOOGLE CLASSROOM ON EQUALITY EDUCATION IN PKBM USING THE TECHNOLOGY ACCEPTANCE MODEL APPROACH - Tarekah Hasanah (Jurnal TAM (Technology Acceptance Model), 2026)
This study aims to evaluate the success of Google Classroom implementation in non-formal education (PKBM) using the Technology Acceptance Model (TAM) approach. A quantitative survey method was employed with 76 PKBM students as respondents. The variables examined include Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Behavioral Intention (BI), and Actual System Use (ASU). Data were collected using a Likert-scale questionnaire and analyzed through SEM-PLS. The results indicate that PEOU significantly influences PU (β = 0.68; p < 0.001), while both PEOU and PU significantly affect BI (β = 0.41 and β = 0.52; p < 0.001). Furthermore, BI has the strongest influence on ASU (β = 0.73; p < 0.001). The coefficient of determination reveals that the model explains 64% of the variance in BI and 53% in ASU. These findings suggest that perceived ease of use and perceived usefulness are key determinants in enhancing users’ behavioral intention, which subsequently drives successful system implementation. This study contributes to the extension of TAM in non-formal education contexts and provides practical insights for technology-based learning implementation in PKBM.